EVALUATION OF EFFICACY OF DIFFERENT MODALITIES IN TREATMENT OF FRACTURE METATARSAL - KAUSHIK, SATYAPRATEEK; RK, VERMA; SP, GUPTA; RAJKUMAR, BHAIRWA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: This study mainly aims to evaluate the efficacy of three different modalities in treatment of fracture metatarsal. Methods: A hospital-based prospective comparative study was conducted in Mahatma Gandhi Medical College, Jaipur, from December 2018 to June 2020, involving 50 patients above 16 years of age presented with isolated metatarsal fractures and grade I open fractures were included in the study. Patients fulfilling the inclusion criteria were then allocated to one of three groups. Group A – Conservative management, Group B – K-wire fixation, and Group C – external Fixator. Outcome measurement was done using AOFAS MID FOOT SCALE (100 points total). Results: Majority of 29 patients belong to 35–60 years of age group followed by 18 patients in 26–35 years. Maximum number of cases is reported in male category that was 45 cases. Majority of the cases falls under the category of road traffic accidents that are 28 cases which is about 56% of the total cases. In 37 cases right foot was involved, whereas 13 cases are on the left side, suggesting the right was the dominant side. About 48% of the second metatarsal and 30% of the third metatarsal showed the maximum involvement. Maximum number of cases were designated as excellent having score between 90 and 100 that was about 38 cases which are 76% of total cases suggesting every treatment modality was good in its own right. There was a significant difference between the different treatment modalities at final follow-up p<0.05. Conclusion: All treatment modalities equally good, achieving good fracture union, decreased incidence of pain, and achieve a good range of movements, but complications rate was more in the conservative group as compared to other groups.